Savage imaginings : historical and contemporary constructions of Australian Aboriginalities - Russell, Lynette (Melbourne : Australian Scholarly Publishing, 2001)
This book explores the dominant discussions in Australian Aboriginal history. Its central tenet is that European textual representations of Aboriginal Australians have characteristically involved images and imaginings of primitivism, great antiquity and sameness. The author argues that Aboriginal-focussed museum displays, textual studies and photo-essays have reduced Aboriginal culture to a moment frozen in pre-contact time.
1. Australian modernity, post-colonialism and discourses of Aboriginality -- 2. Walkabout: the popular view -- 3. Images of power: colonial relationships and museum representations of Aboriginal Australia -- 4. Koori modernity and corporate identity -- 5. Epilogue: re-presented pasts.
Includes index.
Bibliography: p. 115-129.
Keywords: Aboriginal Australians -- Attitudes; Aboriginal Australians -- Ethnic identity; Race relations - Racism - Stereotyping; Social identity - Aboriginality; Archaeology - Theory and criticism; Race relations - Representation - History; Social identity; Race relations - Representation; Attitudes - Indigenous perspectives